Authorship Trend and Collaborative Research in Genetics and Plant Breeding - Kumbar, Mallinath; Girish Kumar, N. (Journal of Information and Knowledge, 2013)
Study attempted to identify the authorship trend and collaborative research in Genetics and Plant Breeding, based on the data collected from the Indian Journal of Genetics and Plant Breeding published during 1998-2002. The study reveals that two authors papers are maximum 215 (44.24%). The degree of collaboration in research is 0.87 in genetics and plant breeding as a whole and ranged between 0.86 to 0.89 during 1998-2002. The contribution from research institutions and laboratories i.e., 216 (44.08%) is vividly ahead of other segments such as universities and colleges. 475 articles contributed by the Indian authors and a significant percent i.e., 107 (22.49%) is reported from Delhi State.